MODEL PEMBELAJARAN TEMATIK INTEGRATIF MATEMATIKA TEMA OPERASI HITUNG DENGAN PENDEKATAN BAYANI, BURHANI, IRFANI - zumratun, zumratun; jamiin, jamiin (STIT Sunan Giri Bima, 2020)
Speaking on integrative thematic issues, it is inseparable from the 2013 curriculum. It is said so because the content or content of lessons in class presentations has been polished into one theme in which there are several subjects that have been integrated and one of them is the integration of Religion with Mathematics . The idea of ​​integration of religious and general values ​​is not a discourse to achieve academic sympathies, but rather an urgent need that must be carried out as a guide to existing education, given that education has been influenced by a strong dualism between the religious sciences and general sciences. In addition, the degradation of ethical values, morals and character of students also makes it a necessity for an institution to continue to teach all students about values ​​without ignoring general lessons. So by presenting the integration of religious subjects and general subjects (mathematics), it is expected that all students have character values ​​in themselves. This suggests that the implementation of Islamic education has a strategic portion in complementing the general education curriculum. That is, the learning process between general education and religion becomes the main process in creating human resources with the insight of science and technology, so that the added values ​​obtained by students with the implementation of Islamic learning which certainly leads to the cultivation of morals, morals, and behavior of participants better students.